THE ROLE OF JULO-JULO IN OVERCOMING THE NEGATIVE IMPACT OF MONEY LENDER PRACTICES ON COMMUNITY ECONOMIC DEVELOPMENT - Replita Replita; Nursyirwan Effendi; Taufika Ophiyandri; Djuljastri Abdul Rajak; Alfan Miko (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2025)
The practice of loan sharks in low-income communities results in economic dependence and long-term financial difficulties. The presence of Julo-Julo as a community-based traditional financial institution becomes an important alternative that can provide more humane and socially just financial solutions. The purpose of this study is to understand the role of Julo-Julo in the economic development of the community, especially at the grassroots level. This study uses a qualitative descriptive approach, with data that cannot be measured on a numerical scale. Research results state the role of Traditional Julo-Julo in overcoming the negative impacts of loan shark practices by reducing risks, conducting socialization, and providing the best services. The strategy of Traditional Julo-Julo is to keep the community away from usury practices by implementing a proactive approach and freeing the community from dependence on loan sharks.